Clinical Safety Outcomes in Patients With Nonvalvular Atrial Fibrillation on Rivaroxaban and Diltiazem. Issue 1 (January 2019) - Bartlett, Jenna W.; Renner, Elizabeth; Mouland, Erin; Barnes, Geoffrey D.; Kuo, Liane; Ha, Nghi B.
Background: It is unknown whether diltiazem, a moderate cytochrome P450 enzyme (CYP3A4) and P-glycoprotein (P-gp) inhibitor, increases the incidence of bleeding events in combination with rivaroxaban, a CYP3A4 and P-gp substrate.Objective: To assess major and clinically relevant nonmajor (CRNM) bleeding outcomes in patients with nonvalvular atrial fibrillation (NVAF) on rivaroxaban with concomitant diltiazem in a real-world setting.Methods: This retrospective case-cohort study included adult patients with NVAF prescribed both rivaroxaban and diltiazem for at least 30 days. Patients were matched 1:1 by age and baseline creatinine clearance (CrCl) to control patients taking rivaroxaban alone. The primary outcome was the composite of major and CRNM bleeding. Additional outcomes included bleeding events resulting in discontinuation of rivaroxaban, time to first bleeding event, and type of first bleed.Results: A total of 143 cases and 143 controls were included. The mean age was 69 years and median baseline CrCl was 87 mL/min. Median follow-up time was 12.4 months for cases and 16.5 months for controls. There was no significant difference in proportion of patients experiencing a major and/or CRNM bleeding event between cases and controls: 23.1% versus 28.0%, respectively; 9 cases and 8 controls permanently discontinued rivaroxaban because of bleeding. Gastrointestinal/rectal bleeding and hematuria were the most frequently reported bleeding events in both groups.Conclusion and Relevance: This is the first study to assess major and CRNM bleeding outcomes in patients with NVAF on rivaroxaban and diltiazem. Diltiazem use was not associated with an increased rate of bleeding events.